Urgensi Musyawarah dalam Alqur'an (Kajian Tafsir Tematik) - Zamakhsyari Abdul Majid (STAI ALHIKMAH Jakarta, 2019)
The purpose of this writing is motivated by the change in paradigm and system of freedom in opinion, equality and fairness towards social behavior in the society. This study measures, compares and analyzes the principles of deliberation in the dimensions of Al-Qur'an, as well as comparing scientific principles that are sourced from the West. The influence of cultural acculturation and the development of Western political theory have become an urgency for the democratic system. So that requires an in-depth analysis about the perspective of Al-Qur'an towards deliberation, the position of deliberation in Islam, the principle of deliberation and the urgency of deliberation through the phenomenology of Al- Qur'an in solving that problem. Keywords: Deliberation, Al-Quran, Paradigm, Social Behavior Tujuan penulisan ini dilatarbelakangi oleh perubahan paradigma dan sistem kebebasan berpendapat, persamaan dan keadilan terhadap perilaku sosial di masyarakat. Kajian ini mengukur, membandingkan dan menganalisa prinsip musyawarah dalam dimensi Al-Quran, serta membandingkan kaidah-kaidah keilmuan yang bersumber dari Barat. Pengaruh akulturasi budaya dan perkembangan teori politik Barat telah menjadi urgensi bagi sistem demokrasi. Sehingga memerlukan sebuah kajian analisa yang mendalam tentang perspektif Al-Quran terhadap musyawarah, kedudukan musyawarah dalam Islam, prinsip musyawarah dan urgensi musyawarah melalui fenomenologis Al- Quran dalam menyelesaikan persoalan tersebut. Kata Kunci : Musyawarah, Al-Quran, Paradigma, Perilaku Sosial